A pre-fixing-heat-activating bifunctional self-coating skeleton cord fabric, a preparation method and application thereof

CN122918845APending Publication Date: 2026-10-16ZHONGCE RUBBER GRP CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611167050.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]本发明的技术目的在于提供一种适用于窄幅冠带条裁切的预固持—热活化双功能自涂胶骨架帘布、制备方法及其应用,通过在骨架帘线表面构建低用量、非压敏、兼具预固持相和热活化粘合相的自涂胶双相界面层,使宽幅骨架帘布在未采用纬纱横向固持、未覆盖连续压延橡胶层且未被弹性体胶浆整体包封的条件下,仍能够稳定裁切为窄幅冠带条,并在后续压延、贴合或硫化热史中与橡胶形成可靠粘合,从而解决现有窄幅冠带条裁切散丝、边缘完整性差、贴合操作稳定性不足以及疲劳后粘合保持率下降的问题

Benefits of technology

[0036] The technical advantages of this invention are as follows: By dividing the functions of the pre-fixed phase and the thermally activated adhesive phase, the skeleton fabric obtains fiber bundle constraint and edge retention before the wide-width fabric formation, cutting, transfer and bonding stages, reducing the fraying rate after narrow-width cutting, and improving edge integrity, strip width stability and pre-forming operability; at the same time, the self-adhesive two-phase interface layer remains in a non-pressure-sensitive state before thermal activation, avoiding roll adhesion, storage difficulties and narrowing of the bonding window due to excessively high initial viscosity. Under the heat of subsequent calendering, bonding or vulcanization, the thermally activated adhesive phase softens, flows, unblocks or reacts and forms a reinforced bond with the rubber, so that the narrow-width crown strip has cutting stability, processing operability, initial adhesive strength and adhesion retention rate after dynamic fatigue. Compared to solutions without an interface layer, with only a pre-fixed layer, only a thermally activated adhesive layer, or traditional impregnation layer, this invention does not simply improve the surface adhesion of the fiber. Instead, it systematically solves the process contradiction between wide-width skeleton fabric manufacturing and narrow-width crown strip application through a two-stage interface response mechanism of "stabilizing the fibers first and then bonding". It is applicable to tire skeleton materials such as nylon 66, aramid/nylon composite fiber, and polyester fiber, and can improve the engineering application stability of crown strip, cover layer, or belt reinforcement structure of new energy vehicle tires and high-performance passenger car tires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918845A_ABST
    Figure CN122918845A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of tire skeleton material, fiber-rubber interface adhesion and narrow crown belt processing, and particularly relates to a pre-fixing-heat-activating dual-functional self-gluing skeleton cord fabric, a preparation method and application. The skeleton cord fabric comprises parallelly arranged skeleton cords and a self-gluing dual-phase interface layer arranged on the surface of the skeleton cords, wherein the interface layer comprises a pre-fixing phase and a heat-activating adhesion phase. The pre-fixing phase forms a non-pressure-sensitive continuous constraint film before cutting, so as to reduce the cutting filament and improve the edge integrity; the heat-activating adhesion phase is activated under the heat history of calendering, laminating or vulcanization and forms enhanced adhesion with rubber. The present application can improve the cutting stability, laminating operability, H extraction force and adhesion retention rate after fatigue of the narrow crown belt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical fields of tire skeleton materials, fiber-rubber interface bonding and narrow crown strip processing, and particularly relates to a pre-fixed-heat activated dual-function self-adhesive skeleton cord fabric, its preparation method and application. Background Technology

[0002] With the development of new energy vehicles, high-performance passenger cars, and high-speed radial tires, tires face higher requirements for high-speed durability, handling stability, low rolling resistance, and lightweight structure. The crown layer, cover layer, or localized belt reinforcement layer typically uses reinforcing strips formed from skeleton materials such as nylon 66, aramid / nylon composite fibers, and polyester fibers to limit radial expansion of the tire crown area under high-speed rotation, improving the tire's high-speed uniformity and durability. To meet the needs of precise laying and localized reinforcement during tire molding, in actual production, it is often necessary to further cut the wide skeleton fabric into narrower crown strips, such as 5–15 mm or narrower strips.

[0003] However, traditional wide-width reinforcing cord systems are primarily designed around integral impregnation, integral calendering, and conventional wide-width applications. Their interface treatments typically focus on improving the final adhesion between fibers and rubber, without fully considering issues such as edge fraying, loose fiber bundles, reduced edge integrity, and deformation during transport and bonding when wide cords are cut into narrow strips. Especially when the narrow crown strips are not continuously encapsulated by calendered rubber layers and do not form an integral rubber encapsulation structure, the fiber bundles at the cut edges lack effective constraint, making them prone to fraying, edge curling, unstable strip width, or bonding positioning misalignment during slitting, winding, transport, bonding, and preforming processes. This affects tire forming quality and the reliability of subsequent vulcanization bonding.

[0004] In existing technology, published document KR20190134737A proposes a crown layer reinforcement strip for pneumatic radial tires. It addresses the issues of cord separation and fraying during the cutting, slitting, and winding of narrow crown layer reinforcement strips, employing high-density cotton weft yarns and adhesive materials to hold the warp cords in place. While this approach can improve the lateral separation problem during crown layer cutting and winding to some extent, its technical approach relies heavily on mechanical weft yarn holding and a high content of adhesive material to form a stable overall structure. This can easily increase the complexity of the material structure and may affect strip flexibility, interface uniformity, and the operating window during subsequent tire molding processes. For self-coated skeleton cord fabrics without weft yarn lateral holding and without continuous calendered rubber pre-coating, this solution does not provide technical insights into how to simultaneously achieve pre-holding before cutting and enhanced adhesion after vulcanization heat history using a low-volume interface layer.

[0005] Another prior art, EP3795349B1, discloses a high-adhesion tire cord, which has an adhesive layer on a textile substrate and a latex layer outside the adhesive layer, giving the tire cord better adhesion, thus facilitating stable winding and cutting processes. This approach emphasizes improving processing stability by increasing the surface adhesion of the cord. However, in actual narrow-width crown strip production, relying solely on higher initial adhesion may lead to problems such as roll adhesion, decreased storage stability, and narrowing of the calendering or bonding window. If the interface layer is too hard or used in excessive amounts, it may result in decreased strip flexibility and insufficient adhesion retention after dynamic fatigue. Therefore, simply increasing initial adhesion or using conventional adhesive / latex layers makes it difficult to simultaneously achieve edge retention during the cutting stage, non-pressure-sensitive operability before thermal activation, and enhanced rubber adhesion after vulcanization.

[0006] Therefore, while existing technologies address the issues of filament loosening in narrow-width crown belt strips and rubber bonding in tire cords, they have not fully resolved the process contradiction of needing to stabilize the fibers before and after cutting wide-width skeleton fabric into narrow-width crown belt strips while simultaneously enhancing adhesion during subsequent thermal history. In particular, existing technologies lack a low-volume, non-pressure-sensitive, self-adhesive dual-function interface layer with a pre-fixed holding phase and a thermally activated adhesive phase working in synergy. This layer would provide constraint on the fiber bundles and cut edges during the cutting stage, and then soften, flow, unblock, or react under the thermal history of calendering, lamination, or vulcanization to form a reinforced bond with the rubber.

[0007] Therefore, it is necessary to develop a pre-retaining-thermal-activated dual-function self-adhesive reinforcing cord fabric and its preparation method suitable for narrow-width crown strip cutting. This would reduce the fraying rate after narrow-width cutting, improve edge integrity, transfer bonding stability, thermally activated adhesive strength, and adhesion retention rate after dynamic fatigue, without relying on weft yarn lateral retention and continuous calendered rubber pre-coating. This would meet the stability requirements of crown reinforcement materials for engineering applications in new energy vehicle tires and high-performance passenger car tires. Summary of the Invention

[0008] The technical objective of this invention is to provide a pre-retaining-heat-activated dual-function self-adhesive skeleton fabric suitable for cutting narrow crown belt strips, its preparation method, and its application. By constructing a low-volume, non-pressure-sensitive self-adhesive dual-phase interface layer on the surface of the skeleton cord, which combines a pre-retaining phase and a heat-activated adhesive phase, the wide skeleton fabric can still be stably cut into narrow crown belt strips even without weft yarn lateral fixation, without being covered with a continuous calendered rubber layer, and without being entirely encapsulated by an elastomer adhesive. Furthermore, it forms a reliable bond with the rubber during subsequent calendering, bonding, or vulcanization heat treatment. This solves the problems of loose threads, poor edge integrity, insufficient bonding stability, and decreased adhesion retention rate after fatigue in existing narrow crown belt strip cutting processes.

[0009] Firstly, in order to achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0010] A pre-retaining-heat-activated dual-function self-adhesive bobbin fabric is characterized by comprising multiple bobbin cords arranged parallel to each other along the length of the fabric, wherein the bobbin cords are not laterally fixed by cotton weft yarns, polyester weft yarns, or hot-melt weft yarns; the outer surface of the bobbin cords is provided with a self-adhesive dual-phase interface layer, wherein the self-adhesive dual-phase interface layer comprises 0.8 to 1.1 parts per 100 parts by weight of bobbin fibers, and includes a pre-retaining phase near the surface of the bobbin cords and a heat-activated adhesive phase located outside the pre-retaining phase;

[0011] The pre-fixed phase, after drying or pre-curing at 120–135°C, forms a non-pressure-sensitive continuous constraint film before thermal activation. This film is used to constrain the fiber bundles at the cut edge when the skeleton fabric is cut without being covered by a continuous calendered rubber layer and without being entirely encapsulated by the elastomer mortar.

[0012] The thermally activated adhesive phase comprises at least one of blocked isocyanate, thermally activated phenolic resin, and low-melting-point reactive oligomer, and undergoes unblocking, softening, flow, or reaction under vulcanization heat at 170–180°C to form an adhesive with the rubber.

[0013] As a further improvement, the skeleton cord is selected from at least one of nylon 66 cord, aramid / nylon composite cord, polyester cord, and aramid / polyester composite cord.

[0014] And / or, the pre-retaining phase is selected from at least one of polyurethane, modified polyester, polyamide, acrylate, and epoxidized oligomer;

[0015] And / or, the thermally activated adhesive phase further comprises at least one of a redispersible emulsion, a modified phenolic resin, an epoxy reactive resin, and a rubber-compatible tackifying resin.

[0016] As a further improvement, the mass ratio of the pre-retaining phase to the thermally activated adhesive phase is 45:55 to 40:60;

[0017] And / or, the self-adhesive biphase interface layer is 0.9 to 1.0 parts per 100 parts by weight of the skeleton fiber;

[0018] As a further improvement, the self-adhesive biphase interface layer has a layered structure, which includes a pre-retaining layer directly attached to the surface of the skeleton cord and a heat-activated adhesive layer covering the outside of the pre-retaining layer.

[0019] And / or, the self-adhesive biphase interface layer has a gradient structure, the content of the pre-fixed phase on the side near the surface of the skeleton cord is higher than the content on the outside, and the content of the thermally activated adhesive phase on the outside is higher than the content on the side near the surface of the skeleton cord.

[0020] As a further improvement, after the skeleton fabric is cut into narrow crown strips of 5-10 mm, the loose fiber rate is not higher than 6.9%, the edge integrity rate is not lower than 97%, the H-pulling force after heat activation is not lower than 94 N, and the adhesion retention rate after fatigue is not lower than 93%.

[0021] And / or, the self-adhesive biphase interface layer does not form roll adhesion after being placed at 23°C, and maintains the transport stability, fit positioning and pre-forming operability of the narrow crown strip before thermal activation;

[0022] And / or, the skeleton curtain is a wide skeleton curtain before cutting, and the surface of the wide skeleton curtain is not provided with a continuous rubber sheet layer covering the upper and lower surfaces.

[0023] A narrow crown strip, characterized in that it is obtained by longitudinally cutting the skeleton cord fabric as described in any one of claims 1 to 5, wherein the narrow crown strip is used for the crown layer, cover layer or belt layer reinforcement structure of a tire; preferably, the width of the narrow crown strip is 5 to 10 mm, and it does not contain a continuous calendered rubber layer covering its upper and lower surfaces before being bonded to the tire semi-finished product.

[0024] Secondly, the present invention also provides a method for preparing the skeleton curtain fabric, comprising the following steps:

[0025] S1. Perform at least one of the following pretreatments on the skeleton cord: desizing, cleaning, plasma treatment, corona treatment or surface activation treatment.

[0026] S2. Apply a self-adhesive treatment liquid containing a pre-retaining phase and a thermally activated adhesive phase to the surface of the skeleton cord, so that the formed self-adhesive biphase interface layer is 0.8 to 1.1 parts per 100 parts by weight of the skeleton fiber.

[0027] S3. Arrange the treated skeleton cords into a wide skeleton fabric and dry or pre-cur it at 120-135℃ to form a non-pressure-sensitive continuous constraint film before thermal activation of the pre-fixed phase.

[0028] S4. In the state where the wide skeleton fabric is not covered by the continuous calendered rubber layer and is not completely encapsulated by the elastomer adhesive, the wide skeleton fabric is cut into narrow crown strips of 5-10 mm.

[0029] S5. During calendering, lamination, or vulcanization, the heat-activated adhesive phase is deactivated, softened, flowed, or reacted at 170–180°C, and then bonded to the rubber.

[0030] As a further improvement, in step S2, the self-adhesive treatment liquid is applied to the surface of the skeleton cord by dip coating, scraping, spraying, roller coating or a combination thereof.

[0031] And / or, the drying or pre-curing time in step S3 is 20–300 s, and the thermal activation time in step S5 is 20–180 s;

[0032] Preferably, in step S2, a first treatment liquid containing a pre-retaining phase is applied first, followed by a second treatment liquid containing a thermally activated adhesive phase, to form a pre-retaining layer near the surface of the skeleton cord and a thermally activated adhesive layer located outside the pre-retaining layer.

[0033] Preferably, in step S2, the pre-fixed phase and the thermally activated binder phase are configured as the same treatment liquid, and a gradient structure with varying content from the inside to the outside is formed through compatibility differences, drying migration, or curing shrinkage.

[0034] Thirdly, the present invention also provides a tire in which the crown layer, cover layer or belt layer reinforcement structure includes the aforementioned narrow crown strip.

[0035] Thirdly, the present invention also provides the application of the skeleton fabric or the narrow crown strip in new energy vehicle tires or high-performance passenger car tires, which can improve the cut edge integrity, bonding operation stability, thermally activated adhesive strength and dynamic fatigue adhesive retention rate of the narrow crown strip under the condition that the weft yarn is not used for lateral fixation and the continuous calendered rubber layer is not used for pre-coating.

[0036] The technical advantages of this invention are as follows: By dividing the functions of the pre-fixed phase and the thermally activated adhesive phase, the skeleton fabric obtains fiber bundle constraint and edge retention before the wide-width fabric formation, cutting, transfer and bonding stages, reducing the fraying rate after narrow-width cutting, and improving edge integrity, strip width stability and pre-forming operability; at the same time, the self-adhesive two-phase interface layer remains in a non-pressure-sensitive state before thermal activation, avoiding roll adhesion, storage difficulties and narrowing of the bonding window due to excessively high initial viscosity. Under the heat of subsequent calendering, bonding or vulcanization, the thermally activated adhesive phase softens, flows, unblocks or reacts and forms a reinforced bond with the rubber, so that the narrow-width crown strip has cutting stability, processing operability, initial adhesive strength and adhesion retention rate after dynamic fatigue. Compared to solutions without an interface layer, with only a pre-fixed layer, only a thermally activated adhesive layer, or traditional impregnation layer, this invention does not simply improve the surface adhesion of the fiber. Instead, it systematically solves the process contradiction between wide-width skeleton fabric manufacturing and narrow-width crown strip application through a two-stage interface response mechanism of "stabilizing the fibers first and then bonding". It is applicable to tire skeleton materials such as nylon 66, aramid / nylon composite fiber, and polyester fiber, and can improve the engineering application stability of crown strip, cover layer, or belt reinforcement structure of new energy vehicle tires and high-performance passenger car tires. Attached Figure Description

[0037] Figure 1 This is a comparison chart of the fraying rate and H-pulling force after the key sample is cut.

[0038] Figure 2 The figure shows the effect of thermal activation temperature on edge integrity and adhesion retention after fatigue.

[0039] Figure 3 This is a comparison chart of the overall performance of the examples and comparative examples.

[0040] Figure 4 The graph shows the effect of the self-adhesive two-phase interface layer dosage window on the filament rate and H-pulling force.

[0041] Figure 5 This is a flowchart of the process for preparing the skeleton curtain fabric and cutting it into narrow widths. Detailed Implementation

[0042] The present invention will be further described below with reference to the accompanying drawings, embodiments, and comparative examples. It should be understood that the following specific embodiments are used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Any equivalent substitutions or conventional adjustments made within the scope of the present invention to the type of skeleton cord, the specific resin type of the self-adhesive two-phase interface layer, the application method, the drying or pre-curing method, the thermal activation method, and the tire molding process should fall within the scope of protection of the present invention.

[0043] In this embodiment, "skeleton cord" refers to organic fiber cord used in the reinforcement structure of tire crown layer, cover layer, or belt layer, including but not limited to nylon 66 cord, aramid / nylon composite cord, polyester cord, or aramid / polyester composite cord. "Self-adhesive dual-phase interface layer" refers to an interface layer pre-set on the outer surface of the skeleton cord, which has a pre-holding effect during the cutting stage and a rubber bonding effect under subsequent heat treatment. The self-adhesive dual-phase interface layer differs from traditional continuously calendered rubber layers and from thick rubber coating layers that encapsulate multiple cords entirely in an elastomer adhesive. Its dosage is low, preferably 0.8 to 1.1 parts per 100 parts by weight of skeleton fiber, more preferably 0.9 to 1.0 parts.

[0044] In this embodiment, the "pre-retaining phase" refers to a component that can form a continuous or partially continuous restraining film on the surface of the skeleton cord before thermal activation. Its main function is not to provide high initial viscosity, but to provide restraint to the cord bundles and fiber bundles at the cut edges before the wide-width skeleton fabric is formed, slit, wound, transported, and laminated, thereby reducing the fraying rate and improving the edge integrity rate. The pre-retaining phase is preferably one or more of polyurethane, modified polyester, polyamide, acrylate, and epoxidized oligomers.

[0045] In this embodiment, the "thermally activated adhesive phase" refers to a component that softens, flows, deseales, migrates at the interface, or reacts during calendering, lamination, or vulcanization, and forms a reinforcing bond with the rubber. The thermally activated adhesive phase is preferably one or more of the following: blocked isocyanate, thermally activated phenolic resin, low-melting-point reactive oligomer, redispersible emulsion, modified phenolic resin, epoxy reactive resin, and rubber-compatible tackifying resin.

[0046] In this embodiment, "non-pressure sensitive" means that the self-adhesive two-phase interface layer does not exhibit significant pressure-sensitive adhesive adhesion during room temperature storage, winding, and transportation, does not cause interlayer adhesion in the roll, and does not lead to slitting tool adhesion, strip dragging deformation, or difficulty in bonding and positioning due to excessively high initial tack. "Thermal activation" means that under the influence of temperature during subsequent calendering, bonding, or vulcanization processes, the thermally activated adhesive phase changes from a relatively stable state to a state in which it can wet, diffuse, react, or synergistically bond with the rubber.

[0047] I. Experimental Materials, Equipment and Testing Methods

[0048] The experiments in this embodiment were conducted on a small-scale laboratory test line. The main reinforcing cord used in the experiments was nylon 66 cord, with some embodiments using aramid / nylon composite cord. Nylon 66 cord, as a commonly used reinforcing material for tire crown belt layers, exhibits good thermal stability, dimensional stability, and dynamic fatigue adaptability; the aramid / nylon composite cord was used to verify the applicability of the composite reinforcing material to the present invention.

[0049] The pre-retaining phase A is a blend of waterborne polyurethane and modified polyester. The waterborne polyurethane provides film-forming properties and flexibility, while the modified polyester improves adhesion stability to the surface of polyamide fibers or composite fibers. The heat-activated adhesive phase B is a blend of blocked isocyanate, heat-activated phenolic resin, and low-melting-point reactive oligomers. The blocked isocyanate is unblocked under vulcanization heat and provides reactivity, the heat-activated phenolic resin improves rubber compatibility, and the low-melting-point reactive oligomers improve flow and interfacial wetting during the heat activation stage. Those skilled in the art can routinely adjust the specific resin grades, solid content, and additive ratios of the pre-retaining phase A and the heat-activated adhesive phase B according to different reinforcing cords and rubber formulations, as long as the dual functional effects of pre-retaining before heat activation and adhesive enhancement after heat activation are achieved.

[0050] The self-adhesive treatment solution described in this embodiment uses deionized water as the dispersion medium, and the solid content is controlled within a suitable range to form a low-volume interface layer on the surface of the skeleton cord through dip coating, scraping, spraying, or roller coating. To avoid obvious pores, lumps, or uneven surfaces during the drying process, the viscosity of the treatment solution is controlled in the experiment to ensure that it can uniformly wet the skeleton cord and form a continuous constraint film in the subsequent drying or pre-curing stages.

[0051] Pretreatment of the bobbin cord includes desizing, cleaning, and surface activation. Specifically, the bobbin cord is unwound under low tension and passed through a cleaning zone to remove surface dust, oil residue, and processing impurities. If necessary, plasma treatment or corona treatment can be performed to improve the adhesion stability between the self-adhesive dual-phase interface layer and the bobbin cord. After pretreatment, the bobbin cord remains parallel and is not laterally secured with cotton weft yarns, polyester weft yarns, or hot-melt weft yarns.

[0052] The self-adhesive two-phase interface layer can be formed in two ways. The first method is a layered application method, where a first treatment liquid containing pre-retaining phase A is applied, followed by preliminary drying, and then a second treatment liquid containing thermally activated adhesive phase B is applied, thus forming a pre-retaining layer near the surface of the skeleton cord and a thermally activated adhesive layer on the outside. The second method is a blending application method, where pre-retaining phase A and thermally activated adhesive phase B are mixed in the same treatment liquid. Through their compatibility differences, drying migration, and curing shrinkage, a gradient structure is formed in the thickness direction of the interface layer, with the inner pre-retaining phase relatively enriched and the outer thermally activated adhesive phase relatively enriched.

[0053] In the preparation of wide-width skeleton cord fabric, the treated skeleton cords are arranged parallel along their length to form a wide-width skeleton cord fabric. Before cutting, this wide-width skeleton cord fabric is not covered with a continuous calendered rubber layer, nor is an elastomer adhesive used to encapsulate multiple cords as a whole. After drying or pre-curing, the pre-retaining phase forms a non-pressure-sensitive continuous constraint film on the surface of the skeleton cords before thermal activation. The preferred drying or pre-curing temperature is 120–135°C, and the time is 20–300 s. Within this temperature range, the pre-retaining phase can form a film and provide bundle retention, while the thermally activated adhesive phase does not undergo complete activation, avoiding excessively high initial adhesion before cutting.

[0054] The cutting experiments were conducted using a laboratory slitting machine. Wide-width reinforcing fabric was longitudinally cut into narrow crown strips of varying widths without being covered by a continuous calendered rubber layer or entirely encapsulated by the elastomer adhesive. The cutting widths were set to 20 mm, 15 mm, 12 mm, 10 mm, 8 mm, 6 mm, or 5 mm according to the examples, and the minimum stable width required for stable cutting and winding of different samples was recorded. The cut samples were used to test fraying rate, edge integrity, preforming operability, H-pull-out force, and post-fatigue adhesion retention.

[0055] The fraying rate was tested using a fixed-length sample observation method. A narrow strip of crown band, 1000 mm in length, was cut from each sample and placed on a standard platform. Under magnified observation, the percentage of lengths showing obvious fiber fraying, protrusion, or detachment from the edge contour at the cut edge was counted. Five strips were tested in each group, and the average value was taken as the fraying rate. A lower fraying rate indicates better pre-fixation effect at the cut edge.

[0056] Edge integrity testing employed a combination of image acquisition and manual verification. Continuous photographs were taken of the edges of the cut narrow crown band strips, and the percentage of strips with straight edges, no obvious loose threads, no obvious gaps, and no significant fluctuations in width was recorded. Five strips were tested per group, and the average value was taken as the edge integrity rate. A higher edge integrity rate indicates better geometric stability of the narrow crown band strip during cutting and transport.

[0057] The operability of the preform was evaluated using a comprehensive scoring method. Narrow crown strips were unwound, positioned, lightly pressed, and transported on a laboratory bonding platform to observe for issues such as roll adhesion, unwinding drag, strip twisting, edge lifting, positioning misalignment, or post-bonding springback. The scoring was out of 100 points, with higher scores indicating better preform operability. For this invention, preform operability requires not only stable strip edges but also a non-pressure-sensitive state before thermal activation to avoid narrowing of the bonding window due to excessively high initial viscosity.

[0058] The H-pull-out force test is used to evaluate the adhesion strength between the reinforcing cord and the rubber after heat activation. A narrow crown strip is compounded with a tire crown rubber composition according to a specified method, and then heat-activated or vulcanized at a set temperature. The force required to pull the cord out of the rubber is then tested. At least five samples are tested in each group, and the average value is taken as the H-pull-out force. A higher H-pull-out force indicates a stronger adhesion between the heat-activated binder phase and the rubber.

[0059] Post-fatigue adhesion retention testing is used to evaluate the adhesion reliability of samples under dynamic use conditions. Composite samples that have undergone thermally activated bonding are subjected to dynamic fatigue treatment, and then the H-pull-out force is tested again. The ratio of the post-fatigue H-pull-out force to the initial H-pull-out force is used as the post-fatigue adhesion retention rate. A higher post-fatigue adhesion retention rate indicates that the interfacial layer is less prone to adhesion degradation during the dynamic use of the tire.

[0060] II. Examples 1-8

[0061] Examples 1-8 all utilize the self-adhesive two-phase interface layer of the present invention. The main differences between the examples lie in the skeleton material, the amount of self-adhesive two-phase interface layer used, the mass ratio of pre-fixed phase A to thermally activated adhesive phase B, the pre-curing temperature, the thermal activation temperature, the cutting width of the narrow crown strip, and the interface layer structure. None of the examples used cotton weft yarn, polyester weft yarn, or hot-melt weft yarn for lateral fixation, and all were cut without being covered by a continuous calendered rubber layer or completely encapsulated by the elastomer adhesive.

[0062] Example 1

[0063] In this embodiment, nylon 66 cord is used as the skeleton cord. Based on 100 parts by weight of the skeleton fiber, the amount of the self-adhesive two-phase interface layer is 0.5 parts, and the mass ratio of pre-retaining phase A to thermally activated adhesive phase B is 60:40. After cleaning and surface activation, the nylon 66 cord is coated with a treatment solution containing pre-retaining phase A and thermally activated adhesive phase B via dip coating. After pre-curing at 110°C, a wide skeleton fabric is formed, which is then cut into 20 mm narrow crown strips. Subsequently, it is composited with rubber under thermal activation conditions at 150°C, and its performance is tested.

[0064] This embodiment demonstrates that the present invention can still achieve basic cutting stability and subsequent adhesive reinforcement under conditions of lower interface layer dosage and wider stripe. Test results show that Example 1 has a filament rate of 9.8%, an edge integrity rate of 90%, a preform operability score of 82 points, an H-pull force of 84 N, a post-fatigue adhesive retention rate of 85%, and a minimum stable width of 12 mm. Combined with... Figure 1 It can be seen that, compared with the comparison example without an interface layer, Example 1 has significantly improved the cutting of loose fibers and H-pulling force, indicating that the self-adhesive biphase interface layer has practical effect.

[0065] Example 2

[0066] In this embodiment, nylon 66 cord is used as the skeleton cord. Based on 100 parts by weight of the skeleton fiber, the amount of the self-adhesive two-phase interface layer is 0.7 parts, and the mass ratio of pre-fixed phase A to thermally activated adhesive phase B is 55:45. The pre-curing temperature is 120℃, the thermal activation temperature is 160℃, and the cutting width is 15 mm. The remaining preparation steps are basically the same as in Example 1.

[0067] Test results show that Example 2 has a filament rate of 8.6%, an edge integrity rate of 92%, a preform operability score of 85, an H-pull-out force of 89 N, a post-fatigue adhesion retention rate of 88%, and a minimum stable width of 10 mm. Compared with Example 1, increasing the amount of interface layer and appropriately increasing the thermal activation temperature resulted in a decrease in filament rate and an increase in edge integrity rate and H-pull-out force, indicating that adjusting the amount of interface layer and the thermal activation temperature within the scope of this invention can further improve the overall performance.

[0068] Example 3

[0069] In this embodiment, nylon 66 cord is used as the skeleton cord. Based on 100 parts by weight of the skeleton fiber, the amount of the self-adhesive two-phase interface layer is 0.8 parts, and the mass ratio of pre-retaining phase A to thermally activated adhesive phase B is 50:50. The pre-curing temperature is 120℃, the thermal activation temperature is 170℃, and the cutting width is 12 mm.

[0070] Test results showed that Example 3 had a filament rate of 7.4%, an edge integrity rate of 95%, a pre-forming operability score of 88 points, an H-pull force of 93 N, a post-fatigue adhesion retention rate of 91%, and a minimum stable width of 8 mm. Example 3 demonstrates that when the interface layer dosage reaches 0.8 parts and heat activation at 170℃ is used, both the pre-holding effect and the heat-activated adhesion effect are significantly enhanced, allowing narrow crown strips to be stably cut to even smaller widths. Combined with... Figure 2 It can be seen that a temperature around 170℃ is conducive to the full functioning of the thermally activated binder phase.

[0071] Example 4

[0072] In this embodiment, nylon 66 cord is used as the skeleton cord. The amount of self-adhesive two-phase interface layer is 0.9 parts, and the mass ratio of pre-retaining phase A to thermally activated adhesive phase B is 45:55. A layered application method is adopted, first applying the first treatment liquid containing pre-retaining phase A, and then applying the second treatment liquid containing thermally activated adhesive phase B to form a layered structure. The pre-curing temperature is 130℃, the thermal activation temperature is 170℃, and the cutting width is 10 mm.

[0073] Test results showed that Example 4 had a filament loosening rate of 6.9%, an edge integrity rate of 97%, a pre-forming operability score of 90 points, an H-pull-out force of 96 N, a post-fatigue adhesion retention rate of 93%, and a minimum stable width of 6 mm. Example 4 illustrates that arranging the pre-holding phase near the surface of the bobbin thread and arranging the thermally activated adhesive phase on the outside can more clearly achieve the functional division of "inner filament stabilization and outer adhesion." Combined with... Figure 3 It can be seen that Example 4 is superior to the comparative examples of only thermally activated components or only pre-fixed components in terms of cutting stability and adhesion retention.

[0074] Example 5

[0075] In this embodiment, aramid / nylon composite cord is used as the skeleton cord. The amount of self-adhesive two-phase interface layer is 0.8 parts, and the mass ratio of pre-fixed phase A to thermally activated adhesive phase B is 50:50. A layered structure is adopted, the pre-curing temperature is 125℃, the thermal activation temperature is 170℃, and the cutting width is 10 mm.

[0076] Test results show that Example 5 had a filament looseness rate of 7.1%, an edge integrity rate of 96%, a pre-forming operability score of 89 points, an H-pull-out force of 94 N, a post-fatigue adhesion retention rate of 92%, and a minimum stable width of 6 mm. These results demonstrate that the present invention is applicable not only to nylon 66 cords but also to aramid / nylon composite cords. Because the fiber surface characteristics and rigidity of aramid / nylon composite cords differ from those of nylon 66 cords, they still achieve a high edge integrity rate and H-pull-out force, indicating that the present invention has good material adaptability.

[0077] Example 6

[0078] In this embodiment, nylon 66 cord is used as the skeleton cord. The amount of self-adhesive two-phase interface layer is 1.0 part, and the mass ratio of pre-retaining phase A to thermally activated adhesive phase B is 40:60. A layered structure is adopted, the pre-curing temperature is 130℃, the thermal activation temperature is 180℃, and the cutting width is 8 mm.

[0079] Test results showed that Example 6 had a filament rate of 6.2%, an edge integrity rate of 97%, a pre-forming operability score of 91, an H-pull force of 94 N, a post-fatigue adhesion retention rate of 94%, and a minimum stable width of 5 mm. Example 6 demonstrates that when the amount of the self-adhesive biphase interface layer is 1.0 part and the proportion of the thermally activated adhesive phase is increased, the narrow width adaptability is further enhanced, enabling the stable preparation of narrow crown strips with widths of 8 mm and smaller. Figure 4 It can be seen that around 1.0 parts is a relatively optimal dosage window, which can balance the loose fiber rate, H extraction force and operability.

[0080] Example 7

[0081] In this embodiment, nylon 66 cord is used as the skeleton cord. The amount of self-adhesive two-phase interface layer is 1.1 parts, and the mass ratio of pre-retaining phase A to thermally activated adhesive phase B is 45:55. A gradient structure is adopted, that is, by applying the blending treatment liquid, a gradient distribution is formed during drying and pre-curing, with the inner pre-retaining phase relatively enriched and the outer thermally activated adhesive phase relatively enriched. The pre-curing temperature is 130℃, the thermal activation temperature is 175℃, and the cutting width is 6 mm.

[0082] Test results show that Example 7 had a filament loosening rate of 6.0%, an edge integrity rate of 96%, a preforming operability score of 90, an H-pull-out force of 95 N, a post-fatigue adhesion retention rate of 93%, and a minimum stable width of 5 mm. These results demonstrate that the gradient structure can also achieve the functional division of pre-holding and thermally activated adhesion, and is more conducive to stable narrow-width cutting and maintaining adhesion performance compared to a simple homogeneous structure.

[0083] Example 8

[0084] In this embodiment, nylon 66 cord is used as the skeleton cord. The amount of self-adhesive two-phase interface layer is 0.9 parts, and the mass ratio of pre-retaining phase A to thermally activated adhesive phase B is 45:55. A gradient structure is adopted, the pre-curing temperature is 130℃, the thermal activation temperature is 170℃, and the cutting width is 5 mm.

[0085] Test results show that Example 8 has a filament rate of 5.8%, an edge integrity rate of 98%, a preforming operability score of 92, an H-pull force of 98 N, a post-fatigue adhesion retention rate of 95%, and a minimum stable width of 4 mm. Example 8 is the best overall sample in this embodiment. Figure 1 , Figure 3 and Figure 4 It can be seen that Example 8 exhibits excellent performance in terms of cutting stability, edge integrity, H-pulling force, and adhesion retention rate after fatigue, indicating that a better match is formed between the 0.9 parts of interface layer dosage, the 45:55 ratio of pre-retaining phase / thermally activated adhesive phase, 130°C pre-curing, and 170°C thermal activation.

[0086] III. Comparative Examples 1-8

[0087] The comparative examples are used to demonstrate that the technical effect of the present invention is not naturally obtained by any single factor, but is achieved by the combination of a low amount of self-adhesive two-phase interface layer, non-pressure-sensitive pre-fixation before thermal activation, thermal activation bonding under thermal history, and appropriate dosage and temperature window.

[0088] Comparative Example 1

[0089] Comparative Example 1 used nylon 66 cord without any self-adhesive interface layer. The wide skeleton fabric was directly cut into 10 mm narrow crown strips and laminated with rubber at 170°C. Test results showed that Comparative Example 1 had a filament rate of 18.5%, an edge integrity rate of 74%, a pre-forming operability score of 65, an H-pull force of 62 N, a post-fatigue adhesion retention rate of 68%, and a minimum stable width of 20 mm.

[0090] The results indicate that, under the condition of no interface layer, when the wide skeleton fabric is directly cut into narrow crown strips, the fiber bundles at the cut edge lack the necessary restraint, resulting in severe fraying, low edge integrity, and insufficient subsequent rubber bonding strength. Figure 1 Comparative Example 1 showed the highest filament loosening rate and the lowest H extraction force, proving that the pre-fixed-thermally activated dual-functional interface layer is necessary for the purpose of this invention.

[0091] Comparative Example 2

[0092] Comparative Example 2 used nylon 66 cord with a self-adhesive layer of 0.8 parts, but only included a heat-activated adhesive component, without a pre-retaining component. The pre-curing temperature was 120℃, the heat activation temperature was 170℃, and the cutting width was 10 mm. Test results showed that Comparative Example 2 had a filament rate of 13.9%, an edge integrity rate of 84%, a pre-forming operability score of 78 points, an H-pull-out force of 83 N, a post-fatigue adhesion retention rate of 79%, and a minimum stable width of 12 mm.

[0093] The results indicate that while the heat-activated adhesive component alone can improve the H-pulling force to some extent, the lack of pre-holding effect before heat activation still leads to easy loosening of the edge fiber bundles and a relatively high fraying rate during the cutting stage. This comparative example demonstrates that the present invention cannot be simplified to conventional heat-activated adhesive treatment; pre-holding plays an irreplaceable role in ensuring stability during narrow-width cutting.

[0094] Comparative Example 3

[0095] Comparative Example 3 used nylon 66 cord with a self-adhesive layer of 0.8 parts, but only included a pre-retaining component and no heat-activated adhesive component. The pre-curing temperature was 120℃, the heat activation temperature was 170℃, and the cutting width was 10 mm. The test results showed that Comparative Example 3 had a filament rate of 12.4%, an edge integrity rate of 88%, a pre-forming operability score of 82 points, an H-pull-out force of 69 N, a post-fatigue adhesion retention rate of 70%, and a minimum stable width of 10 mm.

[0096] The results indicate that while the pre-retaining component alone can improve cutting stability to some extent, the lack of a thermally activated adhesive phase results in insufficient adhesion enhancement between the component and the rubber, leading to low pull-out force and low adhesion retention after fatigue. This comparative example demonstrates that the present invention cannot be simplified to a simple yarn stabilization process; thermally activated adhesion is necessary for both post-vulcanization adhesion strength and fatigue retention.

[0097] Comparative Example 4

[0098] Comparative Example 4 used nylon 66 cord, with a self-adhesive two-phase interface layer of 0.8 parts. The mass ratio of pre-retaining phase A to thermally activated adhesive phase B was 50:50. The pre-curing temperature was 120℃, but the thermal activation temperature was only 130℃. The cutting width was 10 mm. The test results showed that Comparative Example 4 had a filament rate of 10.8%, an edge integrity rate of 89%, a pre-forming operability score of 81 points, an H-pull force of 75 N, a post-fatigue adhesion retention rate of 76%, and a minimum stable width of 10 mm.

[0099] The results indicate that although a two-phase interface layer is provided, when the thermal activation temperature is too low, the thermally activated binder phase cannot fully soften, unblock, flow, or react, resulting in insufficient adhesion enhancement between it and the rubber. Figure 2 The results show that there is a clear window for the thermal activation temperature, and Comparative Example 4 proves that low-temperature thermal activation cannot fully realize the effect of the present invention.

[0100] Comparative Example 5

[0101] Comparative Example 5 used nylon 66 cord, with a self-adhesive two-phase interface layer of 0.8 parts, a pre-retaining phase A to thermally activated adhesive phase B mass ratio of 50:50, a pre-curing temperature of 120℃, a thermal activation temperature of 200℃, and a cutting width of 10 mm. Test results showed that Comparative Example 5 had a filament rate of 11.5%, an edge integrity rate of 86%, a pre-forming operability score of 76 points, an H-pull-out force of 82 N, a post-fatigue adhesion retention rate of 72%, and a minimum stable width of 10 mm.

[0102] The results indicate that while excessively high thermal activation temperatures may result in some initial adhesion, the interface layer is prone to excessive flow, localized embrittlement, or interface inhomogeneity, leading to decreased edge integrity, poor preform operability, and reduced adhesion retention after fatigue. This comparative example is... Figure 2 Correspondingly, it is proven that the preferred thermal activation temperature of the present invention is 170-180°C, rather than simply increasing the temperature.

[0103] Comparative Example 6

[0104] Comparative Example 6 used nylon 66 cord, with a self-adhesive two-phase interface layer of only 0.3 parts. The mass ratio of pre-retaining phase A to thermally activated adhesive phase B was 50:50. The pre-curing temperature was 120℃, the thermal activation temperature was 170℃, and the cutting width was 10 mm. The test results showed that Comparative Example 6 had a filament rate of 14.2%, an edge integrity rate of 82%, a pre-forming operability score of 74 points, an H-pull force of 71 N, a post-fatigue adhesion retention rate of 77%, and a minimum stable width of 14 mm.

[0105] The results indicate that when the amount of the interface layer is too low, the pre-fixed phase cannot form a sufficiently continuous constraint film, and the thermally activated adhesive phase is also insufficient to form sufficient interfacial adhesion under the heat of vulcanization, thus resulting in insufficient cutting stability and adhesion performance. Figure 4 The samples with low to medium dosages had a higher filament breakage rate and lower H extraction force, consistent with the results of Comparative Example 6.

[0106] Comparative Example 7

[0107] Comparative Example 7 used nylon 66 cord, with 1.3 parts of self-adhesive two-phase interface layer, a mass ratio of pre-retaining phase A to thermally activated adhesive phase B of 45:55, a pre-curing temperature of 130℃, a thermal activation temperature of 170℃, and a cutting width of 10 mm. Test results showed that Comparative Example 7 had a filament rate of 8.1%, an edge integrity rate of 94%, a pre-forming operability score of 72 points, an H-pull-out force of 86 N, a post-fatigue adhesion retention rate of 80%, and a minimum stable width of 8 mm.

[0108] The results indicate that when the amount of interface layer is too high, although the loose fiber rate is reduced, the strip becomes harder, the unwinding and bonding adaptability decreases, and the excessive thickness of the interface layer may lead to stress concentration or fatigue retention after thermal activation. Figure 4 Excessive dosage of the interface layer resulted in decreased operability of the sample, consistent with the results of Comparative Example 7. Therefore, controlling the amount of the interface layer to 0.8–1.1 parts in this invention has clear process significance.

[0109] Comparative Example 8

[0110] Comparative Example 8 used nylon 66 cord with a self-adhesive layer of 0.8 parts. It employed a conventional impregnation layer instead of the pre-retaining-thermal-activated biphase structure of this invention. The pre-curing temperature was 120°C, the thermal activation temperature was 170°C, and the cutting width was 10 mm. Test results showed that Comparative Example 8 had a filament rate of 11.0%, an edge integrity rate of 87%, a pre-forming operability score of 79, an H-pull-out force of 78 N, a post-fatigue adhesion retention rate of 75%, and a minimum stable width of 10 mm.

[0111] The results show that although the traditional impregnation layer can provide a certain fiber surface treatment and rubber bonding foundation, it does not perform functional division for the narrow-width cutting stage and the subsequent thermal history stage. Therefore, it cannot simultaneously achieve low filament loosening, high edge integrity, high H-pulling force and high adhesion retention rate after fatigue.

[0112] IV. Performance Data of Examples and Comparative Examples

[0113] The key design parameters for each embodiment and comparative example are shown in Table 1 below.

[0114] Table 1 Key Design Parameters for Examples and Comparative Examples

[0115]

[0116] The key performance results of each embodiment and comparative example are shown in Table 2 below.

[0117] Table 2 Key performance results of the examples and comparative examples

[0118]

[0119] As shown in Table 2, the average fraying rate of Examples 1-8 was 7.225%, significantly lower than the average fraying rate of 12.55% in Comparative Examples 1-8; the average edge integrity rate of Examples 1-8 was 95.125%, higher than the average edge integrity rate of 85.5% in Comparative Examples 1-8; the average H-pull force of Examples 1-8 was 92.875 N, higher than the average H-pull force of 75.75 N in Comparative Examples 1-8; and the average post-fatigue adhesion retention rate of Examples 1-8 was 91.375%, higher than the average post-fatigue adhesion retention rate of 74.625% in Comparative Examples 1-8. These data demonstrate that the present invention not only improves a single performance indicator but also achieves improvements in cutting stability, edge integrity, thermally activated adhesion strength, and fatigue retention.

[0120] Examples 4-8 are samples within the preferred scope of this invention. Their self-adhesive two-phase interface layer content is 0.8-1.1 parts, pre-curing temperature is 125-130℃, thermal activation temperature is 170-180℃, and they employ a layered or gradient structure. Examples 4-8 have an average filament rate of 6.4%, an average edge integrity rate of 96.8%, an average pre-forming operability score of 90.4 points, an average H-pull force of 95.4 N, an average post-fatigue adhesion retention rate of 93.4%, and an average minimum stable width of 5.2 mm. These results demonstrate that the preferred scheme of this invention can stably support the preparation of 5-10 mm narrow crown strips, meeting the requirements for refined laying and localized reinforcement of tire crown layers.

[0121] Comparing the preferred embodiment 8 with the interface-free comparative embodiment 1, the fraying rate decreased from 18.5% to 5.8%, an absolute reduction of 12.7 percentage points; the edge integrity rate increased from 74% to 98%, an increase of 24 percentage points; the H-pull force increased from 62 N to 98 N, an increase of 36 N; and the post-fatigue adhesion retention rate increased from 68% to 95%, an increase of 27 percentage points. This comparison directly demonstrates that the self-adhesive biphase interface layer has a significant technical effect on solving the problems of fraying and insufficient adhesion when cutting narrow crown strips.

[0122] Comparing Example 8 with Relative Example 2 (only heat-activated bonding), the fraying rate decreased from 13.9% to 5.8%, indicating that even with the presence of a heat-activated bonding component, it is still difficult to control the fraying of edge fiber bundles during the cutting stage when the pre-retaining phase is absent. Comparing Example 8 with Relative Example 3 (only pre-retaining), the H-pull-out force increased from 69 N to 98 N, and the post-fatigue bonding retention rate increased from 70% to 95%, indicating that cutting stability cannot be converted into reliable subsequent bonding when the heat-activated bonding phase is absent. Therefore, the pre-retaining phase and the heat-activated bonding phase of the present invention are not simply parallel components, but rather function separately and synergistically at different process stages.

[0123] The key to this invention lies in the functional division of the self-adhesive two-phase interface layer and the control of the process window. Based on the disclosure in this specification, those skilled in the art can implement this invention according to the following steps: First, select nylon 66, aramid / nylon composite, polyester, or aramid / polyester composite skeleton cord; second, prepare a treatment liquid containing a pre-retaining phase and a heat-activated adhesive phase; then, apply the treatment liquid to the surface of the skeleton cord by dip coating, scraping, spraying, roller coating, or a combination thereof; then, dry or pre-cur at 120–135°C to form a non-pressure-sensitive continuous constraint film before heat activation of the pre-retaining phase; subsequently, cut the wide skeleton cord into 5–10 mm narrow crown strips without covering the continuous calendered rubber layer or being entirely encapsulated by the elastomer adhesive; finally, activate the heat-activated adhesive phase and bond it with the rubber during calendering, lamination, or vulcanization at 170–180°C.

[0124] In the above implementation process, the pre-retaining phase should not be too soft or too sticky. If the pre-retaining phase is too soft, it cannot effectively constrain the fiber bundles during cutting; if the initial viscosity of the pre-retaining phase is too high, it may lead to roll adhesion and bonding difficulties. The thermally activated adhesive phase should also not be activated too early in the pre-curing stage, otherwise it will destroy the non-pressure-sensitive properties before thermal activation; at the same time, it should be fully activated in the vulcanization heat history to ensure that it forms a reinforced bond with the rubber. Therefore, this invention achieves the staged function of "stabilizing the yarn before cutting and bonding during vulcanization" by separately controlling the pre-curing temperature and the thermal activation temperature.

[0125] Regarding the amount of material used, the preferred amount of the self-adhesive biphase interface layer is 0.8 to 1.1 parts per 100 parts by weight of the skeleton fiber. This range ensures that the pre-fixed phase forms a sufficiently continuous constraint film, while also ensuring that the thermally activated adhesive phase provides effective adhesion in subsequent thermal history. Simultaneously, it avoids excessively thick interface layers, which can lead to strip stiffness, inconvenient storage and transportation, reduced bonding operability, and decreased fatigue retention. The test results of Examples 4-8 have demonstrated that this range exhibits good stability.

[0126] VIII. Industrial Applicability

[0127] This invention is applicable to the preparation of narrow strips for tire crown layer, cover layer, or belt layer reinforcement structures, and is particularly suitable for new energy vehicle tires, high-performance passenger car tires, and tire products with high requirements for high-speed durability and crown dimensional stability. This invention does not rely on weft yarn lateral fixation, does not require the formation of a continuous calendered rubber overlay before cutting, and does not require the use of thick rubber paste to integrally encapsulate multiple cords. Therefore, it is compatible with existing skeleton cord processing, wide-width fabrication, slitting, bonding, and vulcanization processes.

[0128] Compared with existing technologies, this invention resolves the contradiction between wide-width skeleton fabric manufacturing and narrow-width crown strip applications through a low-volume self-adhesive biphase interface layer. Before and after cutting, the pre-fixed phase provides constraint on the fiber bundles and cut edges; during subsequent calendering, bonding, or vulcanization heat history, the thermally activated adhesive phase forms a reinforced bond with the rubber. Therefore, this invention can reduce the filament rate of narrow-width crown strips, improve edge integrity and pre-forming operability, and enhance H-pull-out force and post-fatigue adhesion retention, demonstrating clear industrial application value.

[0129] The foregoing description of embodiments of the present invention, through which those skilled in the art are able to implement or use the present invention, will be readily apparent to those skilled in the art. Various modifications to these embodiments will be readily apparent to those skilled in the art. The general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novelty disclosed herein.

Claims

1. A pre-retaining-thermally activated dual-function self-adhesive frame fabric, characterized in that, The device includes multiple skeleton cords arranged parallel to each other along the length of the fabric. The skeleton cords are not laterally fixed by cotton weft yarns, polyester weft yarns, or hot-melt weft yarns. The outer surface of the skeleton cords is provided with a self-adhesive two-phase interface layer. The self-adhesive two-phase interface layer is 0.8 to 1.1 parts per 100 parts by weight of skeleton fibers, and includes a pre-fixing phase near the surface of the skeleton cords and a heat-activated adhesive phase located outside the pre-fixing phase. The pre-fixed phase, after drying or pre-curing at 120–135°C, forms a non-pressure-sensitive continuous constraint film before thermal activation. This film is used to constrain the fiber bundles at the cut edge when the skeleton fabric is cut without being covered by a continuous calendered rubber layer and without being entirely encapsulated by the elastomer mortar. The thermally activated adhesive phase comprises at least one of blocked isocyanate, thermally activated phenolic resin, and low-melting-point reactive oligomer, and undergoes unblocking, softening, flow, or reaction under vulcanization heat at 170–180°C to form an adhesive with the rubber.

2. The frame curtain fabric according to claim 1, characterized in that, The skeleton cord is selected from at least one of nylon 66 cord, aramid / nylon composite cord, polyester cord, and aramid / polyester composite cord; And / or, the pre-retaining phase is selected from at least one of polyurethane, modified polyester, polyamide, acrylate, and epoxidized oligomer; And / or, the thermally activated adhesive phase further comprises at least one of a redispersible emulsion, a modified phenolic resin, an epoxy reactive resin, and a rubber-compatible tackifying resin.

3. The frame curtain fabric according to claim 1, characterized in that, The mass ratio of the pre-retaining phase to the thermally activated adhesive phase is 45:55 to 40:60; And / or, the self-adhesive biphase interface layer is 0.9 to 1.0 parts per 100 parts by weight of the skeleton fiber.

4. The frame curtain fabric according to claim 1, characterized in that, The self-adhesive biphase interface layer has a layered structure, which includes a pre-retaining layer directly attached to the surface of the skeleton cord and a heat-activated adhesive layer covering the outside of the pre-retaining layer. And / or, the self-adhesive biphase interface layer has a gradient structure, the content of the pre-fixed phase on the side near the surface of the skeleton cord is higher than the content on the outside, and the content of the thermally activated adhesive phase on the outside is higher than the content on the side near the surface of the skeleton cord.

5. The frame curtain fabric according to claim 1, characterized in that, After the skeleton fabric is cut into narrow crown strips of 5-10 mm, the loose fiber rate is not higher than 6.9%, the edge integrity rate is not lower than 97%, the H-pulling force after heat activation is not lower than 94 N, and the adhesion retention rate after fatigue is not lower than 93%. And / or, the self-adhesive biphase interface layer does not form roll adhesion after being placed at 23°C, and maintains the transport stability, fit positioning and pre-forming operability of the narrow crown strip before thermal activation; And / or, the skeleton curtain is a wide skeleton curtain before cutting, and the surface of the wide skeleton curtain is not provided with a continuous rubber sheet layer covering the upper and lower surfaces.

6. A narrow crown strip, characterized in that, The narrow crown strip is obtained by longitudinal cutting of the skeleton cord fabric as described in any one of claims 1 to 5, and is used for the crown layer, cover layer or belt layer reinforcement structure of the tire; preferably, the width of the narrow crown strip is 5 to 10 mm, and does not include a continuous calendered rubber layer covering its upper and lower surfaces before being bonded to the tire semi-finished product.

7. A method for preparing the skeleton curtain fabric according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Perform at least one of the following pretreatments on the skeleton cord: desizing, cleaning, plasma treatment, corona treatment or surface activation treatment. S2. Apply a self-adhesive treatment liquid containing a pre-retaining phase and a thermally activated adhesive phase to the surface of the skeleton cord, so that the formed self-adhesive biphase interface layer is 0.8 to 1.1 parts per 100 parts by weight of the skeleton fiber. S3. Arrange the treated skeleton cords into a wide skeleton fabric and dry or pre-cur it at 120-135℃ to form a non-pressure-sensitive continuous constraint film before thermal activation of the pre-fixed phase. S4. In the state where the wide skeleton fabric is not covered by the continuous calendered rubber layer and is not completely encapsulated by the elastomer adhesive, the wide skeleton fabric is cut into narrow crown strips of 5-10 mm. S5. During calendering, lamination, or vulcanization, the heat-activated adhesive phase is deactivated, softened, flowed, or reacted at 170–180°C, and then bonded to the rubber.

8. The preparation method according to claim 7, characterized in that, In step S2, the self-adhesive treatment liquid is applied to the surface of the skeleton cord by dip coating, scraping, spraying, roller coating or a combination thereof; And / or, the drying or pre-curing time in step S3 is 20–300 s, and the thermal activation time in step S5 is 20–180 s; Preferably, in step S2, a first treatment liquid containing a pre-retaining phase is applied first, followed by a second treatment liquid containing a thermally activated adhesive phase, to form a pre-retaining layer near the surface of the skeleton cord and a thermally activated adhesive layer located outside the pre-retaining layer. Preferably, in step S2, the pre-fixed phase and the thermally activated binder phase are configured as the same treatment liquid, and a gradient structure with varying content from the inside to the outside is formed through compatibility differences, drying migration, or curing shrinkage.

9. A tire, characterized in that, Its crown band, covering layer, or band reinforcement structure includes the narrow crown band strip as described in claim 6.

10. The application of the skeleton cord fabric according to any one of claims 1 to 5 or the narrow crown strip according to claim 6 in new energy vehicle tires or high-performance passenger car tires, characterized in that, This material is used to improve the cut edge integrity, bonding operation stability, thermally activated adhesive strength, and adhesion retention rate of narrow crown strips without the use of weft yarn lateral fixation and continuous calendered rubber pre-coating.

Citation Information

Patent Citations

  • Tire cord having high adhesion and method of preparing the same

    EP3795349B1